Wait and silence? From the Penelopes of The Odyssey (I. 358-360, II. 104-105 and XIX. 149-150) to the Costa Rican Penelopes - Arroyo-Carvajal, Yordan (2022)
This paper analyzes, from a selection of poems written by seven Costa Rican women authors, two mythemes (waiting and silence), of the mythological figure of Penelope, which arise from narrative tensions in the Odyssey. Approaches are developed around this character and on the terms “poetry and postmodern poets”, “literature written by women” and “mythemes”, which serve as support for the final discussion. As part of the conclusions, just as in the Odyssey there was not a single version of Penelope, neither was there a single version in the poetry written by Costa Rican women